Toward A Comprehensive Framework for The Regulation of IoT Devices in Indonesia: A Taxonomic Analysis - Isman, I; Novita, N (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This study aims to devise a regulatory framework for IoT devices in Indonesia via taxonomic analysis. Taxonomic analysis is the methodological approach to discern pivotal dimensions imperative for comprehensive IoT regulations. The outcomes underscore the imperative for regulatory inclusivity across boundaries to address the intricate nexus of technology, security, and device heterogeneity. The investigation underscores the importance of accessibility, anonymity, and interactivity in safeguarding user access and data within IoT networks. Furthermore, it accentuates the urgency for swift responses to security vulnerabilities. This research posits that Indonesia’s IoT regulations must adeptly navigate the intricacies and dynamism inherent in the IoT landscape while addressing the evolving security challenges within this technological milieu.